2004
DOI: 10.1002/masy.200451128
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Effects on the Crystallization Kinetics and Self‐Nucleation of Double Crystalline Poly(p‐dioxanone)‐b‐poly(ϵ‐caprolactone) Diblock Copolymers

Abstract: The morphology, crystallization and self nucleation behavior of double crystalline diblock copolymers of poly(p‐dioxanone) (PPDX) and poly(ϵ‐caprolactone) (PCL) with different compositions have been studied by different techniques, including optical microscopy (OM), atomic force microscopy (AFM) and differential scanning calorimetry (DSC). The two blocks crystallize in a single coincident exotherm when cooled from the melt. The self‐nucleation technique is able to separate into two exotherms the crystallizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 0 publications
3
41
0
Order By: Relevance
“…In block copolymers, factors such as the volumetric fraction and the degree of segregation affect the type of confinement and, as a consequence, influence the SN behavior. Several works dealing with the crystallization of semicrystalline block copolymers have reported the SN of crystallizable block(s) [3,[94][95][96][97][98][108][109][110][111][112][113][114][115][116][117][118][119]. In these studies, three kinds of behavior have been reported: 1.…”
Section: Influence Of Confinement On Self-nucleation Behaviormentioning
confidence: 99%
“…In block copolymers, factors such as the volumetric fraction and the degree of segregation affect the type of confinement and, as a consequence, influence the SN behavior. Several works dealing with the crystallization of semicrystalline block copolymers have reported the SN of crystallizable block(s) [3,[94][95][96][97][98][108][109][110][111][112][113][114][115][116][117][118][119]. In these studies, three kinds of behavior have been reported: 1.…”
Section: Influence Of Confinement On Self-nucleation Behaviormentioning
confidence: 99%
“…This makes the crystallizable block copolymers representative systems having confined crystallization behavior, especially in the strong segregation regime [52]. Confined crystallization has been widely observed in the diblock copolymers having double crystalline blocks, such as PEO-b-PCL [112][113][114][115][116], PLLA-b-PEO [117][118][119][120][121][122], PLLA-b-PCL [123][124][125], poly(p-dioxanone) (PPDX)-b-PCL [126][127][128], polyolefin-based block copolymers [129][130][131][132][133][134][135], and so on. The confined crystallization kinetics and crystalline morphology of such block copolymers have been extensively studied.…”
Section: Crystalline Morphology Of Polymer Segments Confined In Blockmentioning
confidence: 99%
“…[2][3][4] Although there have been a number of prior reports on double crystalline diblock copolymer systems, the understanding of their complicated properties is still at a nascent stage. [5][6][7][8][9][10][11][12][13][14][15][16] Poly(L-lactide) (PLLA) has been widely employed in the medical field because of its biodegradability. However the applications of PLLA to commercial products are limited principally by its brittleness.…”
Section: Introductionmentioning
confidence: 99%